Equity valuation Siemens AG - Silva, Bernardo Manuel Oliveira Hall Santos Silva (2015)
This dissertation presents an in-depth analysis and consequent equity valuation of Siemens AG. The main objective of this paper is to provide an alternative perspective of what might be the fair value of this company considering its prospects of growth, risk and position in the market. The idea that value is highly subjective is kept in mind during all this process although it is important to understand how crucial this information is to shareholders and potential investors and the necessity of maintaining a neutral position. In order to accomplish what is purposed an overview of the most important valuation techniques and related theory is performed. This part is used as a support for many of the decisions along this dissertation. In the end, the methods and results of this dissertation are compared with those of HSBC in one of their published reports.